For Donation, Organisation, and Nation: Muhammadiyah’s Charity Stamp Program, 1941-1942 - Zara, Muhammad Yuanda (Al-Jami'ah: Journal of Islamic Studies, 2024)
Studies on Muhammadiyah’s charitable works mostly discuss the charitable institutions Muhammadiyah founded, such as hospitals and orphanages, and neglect one-off fundraising activities. This study examines Muhammadiyah’s strategies in promoting ‘Muhammadiyah charity stamps’ to the Netherlands Indies people in 1941. This study shows that although stamps are only small postal items, Muhammadiyah paid great attention to promoting and selling these stamps. It ran a well-organised and national-scale campaign, mobilising its network of branches and groups throughout the Indies. Muhammadiyah used all available campaign media, such as magazines, newspapers, pamphlets, pictures, songs and meetings. To maximise promotion, Muhammadiyah emphasised that buying these charity stamps meant giving donations that Allah would reward, supporting Muhammadiyah’s movements, and helping the welfare of the indigenous people. These charity stamps helped Muhammadiyah raise enormous funds and strengthened its reputation at home and abroad as a social movement that cared for the less fortunate. This study elucidates the largest and most successful one-off charitable fundraising effort, but so far still forgotten in the historiography of Indonesian Islam, which was carried out by an indigenous Muslim socio-religious organisation during the colonial period, using previously overlooked primary documents dating from 1941-1942.[Studi mengenai kiprah Muhammadiyah di bidang amal umumnya membahas tentang institusi amal yang didirikannya, seperti rumah sakit dan panti asuhan. Kegiatan pengumpulan dana yang sifatnya sekali waktu saja banyak diabaikan. Kajian ini membahas strategi Muhammadiyah dalam mempromosikan ‘prangko amal Muhammadiyah’ kepada masyarakat Hindia Belanda pada tahun 1941. Kajian ini menunjukkan bahwa walaupun prangko hanya berupa benda pos kecil, Muhammadiyah memberikan perhatian yang luar biasa untuk mempromosikan dan menjual prangko ini. Organisasi ini menjalankan kampanye yang rapi dan berskala nasional, dengan menggerakkan jaringan cabang dan rantingnya di seluruh Hindia. Muhammadiyah menggunakan segala macam media kampanye yang tersedia, seperti majalah, surat kabar, pamflet, gambar, nyanyian, dan pertemuan-pertemuan. Untuk memaksimalkan promosi, Muhammadiyah menekankan bahwa membeli prangko amal ini berarti melakukan amal yang berpahala, menyokong gerakan sosial Muhammadiyah, dan membantu menyejahterakan masyarakat pribumi. Prangko amal ini membantu Muhammadiyah mengumpulkan dana yang sangat besar dan memperkuat reputasinya di dalam dan luar negeri sebagai gerakan sosial yang menaruh perhatian pada mereka yang kurang beruntung. Kajian ini menerangkan tentang usaha pengumpulan dana amal sekali-waktu yang terbesar dan tersukses, namun sejauh ini masih terlupakan dalam historiografi Islam Indonesia, yang dilakukan suatu organisasi sosial-keagamaan Muslim pribumi pada masa kolonial, dengan menggunakan dokumen-dokumen primer yang berasal dari tahun 1941-1942.]